Anion exchange-induced single-molecule dispersion of cobalt porphyrins in a cationic porous organic polymer for enhanced electrochemical CO2 reduction via secondary-coordination sphere interactions. Issue 36 (7th September 2020) - Tang, Jia-Kang; Zhu, Chen-Yuan; Jiang, Tian-Wen; Wei, Lei; Wang, Hui; Yu, Ke; Yang, Chun-Lei; Zhang, Yue-Biao; Chen, Chen; Li, Zhan-Ting; Zhang, Dan-Wei; Zhang, Li-Ming
Abstract : Anion exchange is a promising strategy to achieve synergistic catalysis via secondary coordination sphere interactions between the catalyst and the support. Abstract : Aqueous electrochemical conversion of CO2 with renewable energy is a sustainable pathway to produce carbon-neutral fuels and address the growing crisis of global warming. A key challenge in the field of electrochemical CO2 reduction (CO2 R) is the design of catalytic materials featuring high product selectivity, stability, and a composition of earth-abundant elements. In this work, we demonstrate anion exchange as a promising strategy to achieve synergistic catalysis via secondary coordination sphere interactions between the catalyst and the support. We encapsulate an anionic cobalt porphyrin-based electrocatalyst, with a single-molecule dispersion, into a cationic porous polymer skeleton, and construct a class of electrocatalysts to convert CO2 to CO with remarkable activity, selectivity and durability. Detailed examination of CO2 R revealed selectivity for CO production in excess of 83% and stability over 7 hours with a per-site turnover frequency of 1.4 s −1 . In situ spectroelectrochemical measurements using surface-enhanced infrared absorption spectroscopy (SEIRAS) provided insights into the capability of the cationic polymer framework to control the interactions of intermediates with groups in close proximity via modifying the secondary coordination sphere interactions around the active sites. Our findings highlight the importance of a rationally designed electrocatalyst/solid support interface and offer a paradigm to integrate catalytically active components and develop efficient electrocatalytic systems via marrying the catalyst and support, and creating synergy.